Financial Fraud Scandal: Motivasi, Konsekuensi dan Upaya Memerangi Fraud - Suryandari, Ni Nyoman Ayu; Gayatri, Gayatri (Jurnal Samudra Ekonomi dan Bisnis, 2022)
The article aims to determine the motivation, consequences and efforts to reduce fraud. The socio-economic impact of the scandal determines whether regulation becomes fundamentally tighter. This study uses a systematic literature review approach with a population of 235 articles published in reputable international journals. Based on the predetermined criteria, sixteen articles were obtained as research samples. As many as 62.5 percent of the articles discussed reviewed the Enron case because it was considered a case that shocked the world, involving companies and public accounting firms that were considered independent parties. The urge to commit fraud can be seen from the internal and external aspects of the company. The consequences of fraud that occur can drag the company and auditors as independent parties. The need for efforts to minimize the occurrence of fraud includes improvements to the company, improvements to the criminal and legislative processes and improvements to individual morality.